Likelihood of propensity to travel: Prediction based on socio-demographic factors - Zahirović, Sejfudin; Okičić, Jasmina; Herić, Mensur; Kakeš, Dino (Hotel and Tourism Management, 2021)
The purpose of this research is to provide some insights into socio-demographic determinants of predicting the likelihood of residents propensity to travel. Using the quota sampling technique, data collection was carried out from October to December 2019, yielding a sample of 632 valid responses. To gain a better understanding of the sociodemographic determinants of propensity to travel, we, primarily, use descriptive statistical analysis, chi-square test and probit regression model. The research findings have revealed that age, education and household income characteristics may be considered as antecedents of travel propensity of residents. Having in mind the impact that Covid-19 pandemic has on sector of tourism worldwide, and based on the results of this research, policymakers‘ efforts should be directed to promoting local tourist destinations and to enhancing tourism literacy of residents.